FAKTOR – FAKTOR PENGARUH AUDIT REPORT LAG (Kajian Empiris Pada Perusahaan manufaktur Yang Terdaftar Di Bursa Efek IndonesiaTahun 2010-2012) - Revani Ratna Sari; Imam Ghozali (Diponegoro Journal of Accounting, 2014)
This study aims to analyze the influence of Profitability, Profit / Loss Current Year, Solvency, Company Size, Audit Opinion, Reputation public accounting firm, to audit the effectiveness of the Audit Committee report lag in companies listed on the Indonesia Stock Exchange in the period 2010-2012. The population of this study adalag entire manufacturing companies listed in Indonesia Stock Exchange in the period 2010-2012. The sample used in this study is as much as 96 companies. Sampling was done using purposive sampling technique. The results of this study indicate that the profit / loss for the year and significant effect on the profitability of the company audit report lag while solvency, company size, public accounting firm's reputation and effectiveness of the Audit Committee does not have a significant impact on audit report lag.